Aplikasi Reservasi Ibadah Mawar Sharon Salatiga Menggunakan Flutter - Davin Kurnia Hiuredhy; Yos Richard Beeh (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Mawar Sharon Church Salatiga has a congregation of more than 300 people registered in the My GMS application provided by the Mawar Sharon Church in West Surabaya. Due to the Covid-19 pandemic, the number of church seats is limited so that many congregations do not get seats. In this study, the GMS Salatiga Worship Reservation application will be designed based on a progressive web application using the Flutter and Firebase frameworks that utilize a real time database. The existence of this application can facilitate seat reservation at Mawar Sharon Church Salatiga. According to the user acceptance test that has been done, as many as 92% of respondents stated that the GMS Salatiga Worship Reservation application is easy to use and the results obtained are that this application is in accordance with the needs of ordering reservation at Mawar Sharon Church Salatiga.